The Effects of Okara Ratio and Particle Size on the Physical Properties and Consumer Acceptance of Tofu - Kay Hyun Joo; William L. Kerr; George A. Cavender (Foods, 2023)
Okara, the solid byproduct of soymilk production, poses a sustainability concern, despite being rich in fiber and other healthful compounds. In this study, the physical properties of tofu made from soymilk fortified with differing levels of okara—either whole or fine (<180 µm)—and made with the traditional coagulant nigari were examined. The yield increased linearly with the okara concentration with values of 18.2–29.5% compared to 14.5% for the control. The initial moisture in the fortified samples was higher than the control (79.69–82.78% versus 76.78%), and both the expressible moisture and total moisture after compression were also greater in the fortified samples. With a few exceptions, the texture parameters did not differ between samples. Dynamic rheology showed that all samples had G′ > G″. The storage moduli increased at different rates during each gelling step, with G′ before and after gelling increasing with the fortification level, and was greater for the samples with fine particles than with whole particles. Consumer sensory panels using the hedonic scale showed traditional tofu had a slightly higher acceptability, but the panelists indicated they would be more willing to purchase okara-fortified tofu because of the health and sustainability benefits it might have. Thus, tofu could be produced with added okara with predictable but not profound changes in its physical properties.